Ocular Inflammation in Uveal Tract in Aged Obese Type 2 Diabetic Rats (Spontaneously Diabetic Torii Fatty Rats). (14th September 2014) - Kemmochi, Yusuke; Miyajima, Katsuhiro; Ohta, Takeshi; Sasase, Tomohiko; Yasui, Yuzo; Toyoda, Kaoru; Kakimoto, Kochi; Shoda, Toshiyuki; Kakehashi, Akihiro
Abstract : We report uveitis observed in an obese type 2 diabetes rat model, Spontaneously Diabetic Torii Lepr fa (SDT fatty) rats aged over 50 weeks. The eyes of SDT fatty rats (16 animals: 7 males and 9 females with 50 or 60 weeks of age) were examined histopathologically. Infiltration of inflammatory cells in the uveal tract was observed in 13 of 16 animals. One female showed severe inflammation affecting the entire uveal tract including the iris, ciliary body, and choroid with a variety of inflammatory cells (neutrophils, lymphocytes, and macrophages). Those changes clinically mimic the findings of diabetic iridocyclitis in diabetic patients. Uveitis associated with diabetes can occur in diabetic patients but the pathogenesis still remains unknown. Since increased extramedullary hematopoiesis in the spleen and abscess in the genital and lower urinary tracts were observed in some SDT fatty rats, increased susceptibility to infection, prolongation of inflammatory states, and disorders of the immune system were considered to be possible factors of the uveitis in aged SDT fatty rats. There have been few reports on how diabetes has influence on the development of uveitis associated with bacterial infection. The SDT fatty rat can be an animal model to investigate diabetes-associated uveitis.